MASTERING COMPLEX PERFORMANCE TECHNIQUES OF TRADITIONAL SINGING - Yuldashev Makhamadjon Usubjonovich (Sciental Journals Publishing, 2025)
Each master artist formed in maqom singing relies on unique interpretative decorations of their performance styles. These decorations are characteristic of the masters' style, match their voices, and harmonize beautifully in their performances. Therefore, understanding the essence of performance decorations in maqom performance is important for the singer. In maqom performance, there are ornaments that correspond precisely to the interpretation of specific maqoms. They serve to connect the verses of the ghazal with the melody, to harmonize the sound, to acquire a certain meaning. This article discusses the application of various performance ornaments in maqom performance practice, the state of performance, and the mastery of complex performance styles in traditional singing.
Keywords: Maqom (traditional music), tradition, singer, instrumentalist, lament, melisma, appoggiatura, girift (musical ornament), kashish (musical technique).